Climate Change and Rocky Mountain Ecosystems (Advances in Global Change Research, 2018)
This book is the result of a team of approximately 100 scientists and resource managers who worked together for two years to understand the effects of climatic variability and change on water resources, fisheries, forest vegetation, non-forest vegetation, wildlife, recreation, cultural resources and ecosystem services. Adaptation options, both strategic and tactical, were developed for each resource area. This information is now being applied in the northern rocky Mountains to ensure long-term sustainability in resource conditions. The volume chapters provide a technical assessment of the effects of climatic variability and change on natural and cultural resources, based on best available science, including new analyses obtained through modeling and synthesis of existing data. Each chapter also contains a summary of adaptation strategies (general) and tactics (on-the-ground actions) that have been developed by science-management teams.